Development of all-fiber nanosecond oscillator using actively Q-switched technologies and modulators. (January 2023) - Chen, Xuechun; Wang, Nan; He, Chaojian; Lin, Xuechun
Highlights: Overall progress and development prospects for nanosecond active Q-switched all-fiber oscillators. Detailed classifications, analysis, and outlook of active Q-switching technologies. Detailed analysis and summary of Q-factor optical modulator. Abstract: One of the nanosecond pulse output strategies for fiber lasers with controlled frequency is active Q-switching. Low-cost, high-power efficiency, stable cavity, and customizable pulse output can all be met by a fiber laser with strictly all-fiber Q-factor modulators and appropriate Q-switching techniques. Much research is being conducted to achieve active Q-switched operation with an all-fiber structure in the pursuit of a robust system. Technologies and modulators for active Q-switching in all-fiber structures thus complement and promote each other. This work reviews all-fiber actively Q-switched oscillators' development and research status, introduces various active Q-switching technologies and Q-factor optical modulators in chronological order, and looks forward to future development.